An analysis of the laws governing police misconduct in Malaysia / Azriq Ezanie Satar Aznee, Muhammad Uzair Abd Munir and Uza Najiera Mohd Anuar - Satar Aznee, Azriq Ezanie; Abd Munir, Muhammad Uzair; Mohd Anuar, Uza Najiera (2013)
This research focuses on the analysis of the laws governing police misconduct in Malaysia. The most important law that has been enacted by the parliament in order to govern police misconduct is the Enforcement Agency Integrity Commission (EAIC) Act 2009.Despite the establishment of the Enforcement Agency Integrity Commission (EAIC) Act 2009, the function, reliability and power of the Act to govern police misconduct has become a huge debate amid a rise in custodial deaths.The other laws that have the same objective as this act are the Penal Code, the Federal Constitution, the Police Act 1967 and the Criminal Procedure Code. In order to examine the laws, a comparison analysis is conducted with other selected jurisdictions, namely the United Kingdom, the United States and Australia. The findings of this research revealed that, the laws in Malaysia, particularly the Enforcement Agency Integrity Commission (EAIC) Act 2009 are insufficient in governing police misconduct. The research also revealed that there are many challenges and concerns in governing police misconduct. One of them is the delay of the punishment in passing the proposed Bill of Independent Police Complaints and Misconduct Commission (IPCMC). In addition, two respondents have been interviewed in order to address the problems relating to the current laws governing this issue. The research suggests that the Enforcement Agency Integrity Commission (EAIC) Act 2009 needs to be reviewed in order to improve the governance of police misconduct. It is hoped that this research would assist the policy maker to review such law in Malaysia.